Pengembangan Produk dan Uji Hedonik Madu Hutan dari Apis sp. Dengan Penambahan Ekstrak Strawberry dan Melati - Soegiantoro, Didiek Hardiyanto; Widhiarso, Ari; Damayanti, Sindi; Maharani, Cintia; Prameswari, Laura Dyah; Tudang, Cesy; Abigael, Eltri (Universitas Aufa Royhan, 2024)
The use of honey as a traditional medicine has been known by the community. Forest honey is considered better and more efficacious than cultivated honey because it has a higher content of efficacious compounds with a lower water content. The development of forest honey products with the addition of natural ingredient extracts is considered to be able to increase market potential because it increases health benefits. The problem studied is the market response to forest honey products with the addition of natural ingredient extracts using hedonic test parameters. The aim is to see the market potential for the acceptance of this product. The method used for forest honey production through the honey processing stage to minimize the enzymatic process, the addition of natural ingredient extracts, packaging with primary single-drinking sachet packaging and secondary packaging, and marketing. The results of the study showed that the hedonic test of forest honey products with the addition of natural ingredient extracts received a very good response, where most respondents stated that their responses were really liked and liked. The strawberry extract variant is preferred over jasmine extract, while the packaging can still be improved to attract more consumers. Marketing strategies need to be developed more variedly by utilizing the existing marketing mix. The conclusion is that forest honey products with the addition of natural ingredient extracts packaged in single-drinking sachet packaging have great potential to be developed with several modifications to the packaging and marketing strategies.